Serpentine microfluidic structures for concentration rradient generators - Zaidon, Nuradawiyah; Nordin, Anis Nurashikin; Ismail, Ahmad Faris; Mak, Wing Cheung (IEEE, 2016)
This paper presents microfluidic concentration gradient generator having tree-like structures with implementation of laminar flow concept and small-scale mixing through diffusion inside its microchannel. The microchannels aim for constant flow rate at each outlet and is achieved by optimizing the channel lengths. The generation of concentration gradients is achieved at the outlet by simply tuning the flow rate and geometries of the microfluidics network. Variations in channel dimension and geometry demonstrates possible combinations of the microfluidics network is simulated using circuit simulator, PSpice and computational fluid dynamic (CFD) analysis software, Fluent 14.5. Next, PDMS-based microfluidic chips are fabricated by using soft lithography technique. The simulation and experimental results showed that the prominent mixing behaviour can be obtained inside the serpentine channels with constant flow rate at each outlet.